EVALUASI PROGRAM PENGEMBANGAN WISATA KAMPUNG PELANGI DI KOTA SEMARANG - Anugerah Abdi Widyastuti; Hardi Warsono (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2026)
This research is motivated by the transformation of Wonosari Village into Kampung Pelangi, a thematic tourism destination in Semarang City, aimed at improving environmental quality while enhancing community welfare. Although initially successful in attracting public attention and increasing tourist visits, the sustainability of the program faces various challenges. This study aims to evaluate the Kampung Pelangi tourism development program using the program evaluation model according to D. L. Stufflebeam (2013) and analyze the driving and inhibiting factors. The research method used is descriptive qualitative with data collection techniques through in-depth interviews, observation, and documentation. The results show that conceptually, tourism development is relevant to the characteristics and potential of the region. However, its development has been optimal in terms of context, process, and product, but still less than optimal in terms of input. The factors contributing to driving are community participation, government support, and organizational structure. Meanwhile, the factors contributing to inhibiting are human resources and communication. Therefore, institutional strengthening, increased innovation, and a more integrated sustainability strategy are needed.